Quantifying contaminant losses to water from pastoral landuses in New Zealand II. The effects of some farm mitigation actions over the past two decades. Issue 3 (3rd July 2021) - Monaghan, Ross; Manderson, Andrew; Basher, Les; Spiekermann, Raphael; Dymond, John; Smith, Chris; Muirhead, Richard; Burger, David; McDowell, Richard
ABSTRACT: In New Zealand the primary sector together with central and local government agencies have been promoting measures to mitigate the adverse effect of farming practices on water quality over the last few decades. We assessed the effectiveness of some key measures such as stock exclusion, riparian protection, and nutrient and effluent management on reducing losses of nitrogen (N), phosphorus (P) and sediment to water. Our aim was to determine how much progress has been made in decreasing contaminant discharges between 1995 and 2015 and to determine what the loads would have been if no mitigation had occurred. To do this we estimated losses from 37 dairy and non-dairy/sheep/beef farm typologies that captured the main attributes of production and contaminant loss pathways, nationally. We also accounted for the rate of uptake of measures. Our findings indicated that while the implementation of these measures has helped to reduce P losses (an estimated 20%–25% reduction) to water, they have not been sufficient to off-set estimated increases in N losses (25%) due to expansion of dairy land over the same period. National sediment load is estimated to have decreased (29%) because of afforestation and other soil conservation works.